Bernard Shaw. - Morgan, Margery M. (Writers and their work., 1982)
Bernard Shaw's plays have never ceased to attract a large public, as well as generations of distinguished directors and performers and they continue to be adapted into successful films and musicals. But for many years, even before the critical reaction which followed the dramatist's death, British critics displayed a remarkable lack of interest and were content to leave the judgment and interpretation of his work to American initiative. The present study su.